Enhancing Cognitive Development in Learning Chemical Symbol and Periodicity through Instructional Game - Hassan Aliyu; Yasheni Raman; Corrienna Abdul Talib (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
A digital instructional game with embedded multimedia was believed not limited to allowing the learner to visualize chemistry concepts while playing but enable them to collect relevant information that connects the understanding of the other. The subject was described as a core science area with multiple macroscopic, submicroscopic, and symbolic representations. Thus, the study intended to investigate the effectiveness of the instructional game in enhancing students' cognitive development in learning chemical symbols and periodicity of elements. An instructional tool called